Self-Hybridized Polaritonic Emission from Layered Perovskites - Anantharaman, Surendra B; Stevens, Christopher E; Lynch, Jason; Song, Baokun; Hou, Jin; Zhang, Huiqin; Jo, Kiyoung; Kumar, Pawan; Blancon, Jean-Christophe; Mohite, Aditya D; Hendrickson, Joshua R; Jariwala, Deep (Nano letters, 2021)
Light–matter coupling in excitonic materials has been the subject of intense recent investigations due to emergence of new materials. Two-dimensional layered hybrid organic/inorganic perovskites (2D HOIPs) support strongly bound excitons at room temperature with some of the highest oscillator strengths and electric loss tangents among the known excitonic materials. Here, we report strong light–matter coupling in Ruddlesden–Popper phase 2D HOIP crystals without the necessity of an external cavity. We report the concurrent occurrence of multiple orders of hybrid light–matter states via both reflectance and luminescence spectroscopy in thick (>100 nm) crystals and near-unity absorption in thin (<20 nm) crystals. We observe resonances with quality factors of >250 in hybridized exciton-polaritons and identify a linear correlation between exciton-polariton mode splitting and extinction coefficient of the various 2D HOIPs. Our work opens the door to studying polariton dynamics in self-hybridized and open cavity systems with broad applications in optoelectronics and photochemistry.